The Implementation of Decision-Making Systems to Help Early Detection of Android-Based Child Stunting - Aulia Desy Nur Utomo; Anggi Zafia; Yoso Adi Setyoko (Politeknik Piksi Ganesha Indonesia, 2022)
The deviation of child growth and development is very influential on the growth of children, delays in information on deviations in child growth and development cause delays in actions by Puskesmas (public health center) officers and parents. Therefore, the government routinely conducts screenings for Stimulation of Detection and Early Intervention of Growth and Development (SDIDTK) to find cases of deviations in the growth and development of children aged 3 to 72 months. The screenings aim to detect growth disorders (stunting, thin, thin, fat, microcephaly, and macrocephaly); developmental disorders (rough and smooth movements, speech and language, and social personal); hearing and vision disorders; and emotional mental disorders. To overcome information delays and also child growth and development handlers, an online application to monitor the growth of children aged 0 to 72 months, the M-SDIDTK application was made of which features including (1) an Android-based SDIDTK form that can be downloaded for free by cadres or officers, (2) an SDIDTK screening method guide, (3) and a dashboard of the screening results that Puskesmas officers can access. The dashboard can display a graph of the child's growth development according to the type of developmental disorder based on the SDIDTK book.